Pengembangan Desain Konveyor Berkekuatan Tinggi Untuk Mengangkut Pasir Resin Furan Ke Mesin Penghancur Pasir Menggunakan Metode Ulrich - Riska, Bimmanda Muhammad; Purnomo, Dhika Aditya; Bisono, Fipka; Indrawan, Rizal; Setiawan, Tri Andi; Fajardini, Ridhani Anit; Primaningtyas, Widya Emilia (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Effective machinery and supporting systems significantly influence production capacity, precision, and workflow continuity. In several companies, the lifting of hardened furan sand is still performed using forklifts, leading to delays and reduced efficiency, particularly during night shifts. This condition highlights the need for a more reliable material handling system. This study aims to design a conveyor system capable of transporting hardened sand to the sand crusher machine as an alternative to forklift-based handling. The conveyor is designed to match the height and spatial constraints of the existing sand crusher and can be operated without forklift assistance. The design process includes problem identification, product requirement definition, concept development, and concept evaluation. The results indicate that the second design concept provides the best performance, with a maximum stress of 60.729 MPa, supported by six structural frames, and a total manufacturing cost of Rp 37,923,000. The proposed conveyor system offers a more efficient and practical solution for material handling in sand-processing operations.   Keywords: Manufacturing industry, production efficiency, conveyor system, sand crusher